Performance Evaluation of a Cloud-Integrated IoT Hydroponic System Using Firebase Realtime Database and Netlify Web Dashboard - Ricy Firnando; Prita Salma; Dwi Aurelia Rahmadani; Kemahyanto Exaudi; Rahmat Fadli Isnanto; Andre Hardoni (Journal of Electrical, Electronic, Information, and Communication Technology, 2026)
Smart hydroponic monitoring often relies on third-party mobile applications and faces hardware limitations regarding analog pins on microcontrollers when acquiring data from multiple sensors. Furthermore, technical evaluations regarding the stability of data transmission to the cloud and the response speed of simultaneous sensor readings are rarely discussed. This study aims to evaluate the functionality and responsiveness of hardware integration with the cloud in a hydroponic smart showcase prototype. The NodeMCU ESP8266 microcontroller is used as the central processing unit. To overcome the analog pin limitation for water quality sensors (pH and TDS), the system is integrated with a CD4051BE IC multiplexer. Environmental and nutritional data are transmitted using the API protocol to the Firebase Realtime Database and visualized through a Netlify-hosted web dashboard interface, eliminating mobile application dependency. The high-speed multiplexing mechanism with a 40 ms recording interval was tested over 30 repeated trials per buffer solution. The transient response test recorded a mean error of 0.58 % (SD = 0.27 %) for pH 4.01 solution and 1.21 % (SD = 0.52 %) for pH 6.86 solution. Furthermore, a 10‑hour network stability test (100 samples per sensor) proved that logging transmission to the database ran persistently without packet loss, with average environmental reading errors below 1 % and Wi‑Fi RSSI fluctuations between –45 and –62 dBm. This system demonstrates that a cloud‑based pure web architecture can provide more independent, responsive, and stable IoT control monitoring.